Differential replication of Foot-and-mouth disease viruses in mice determine lethality - Cacciabue, Marco Polo (2017)
Adult C57BL/6J mice have been used to study Foot-and-mouth disease virus (FMDV) biology. In this work, two variants of an FMDV A/Arg/01 strain exhibiting differential pathogenicity in adult mice were identified and characterized: a non-lethal virus (A01NL) caused mild signs of disease, whereas a lethal virus (A01L) caused death within 24–48 h independently of the dose used. Both viruses caused a systemic infection with pathological changes in the exocrine pancreas. Virus A01L reached higher viral loads in plasma and organs of inoculated mice as well as increased replication in an ovine kidney cell line. Complete consensus sequences revealed 6 nonsynonymous changes between A01L and A10NL genomes that might be linked to replication differences, as suggested by in silico prediction studies. Our results highlight the biological significance of discrete genomic variations and reinforce the usefulness of this animal model to study viral determinants of lethality.